Tidepools. Steinbeck locations. - Unknown:::Creator::::::::::::
Tidepool, 1 of 10 Steinbeck locations. This one showing wave crashing into and inundating a tidal area. Mounted on grey-board. See also numbers 0-809, 0-810, 0-811, 0-812, 0-813, 0-814, 0-815, 0-816, 0-817.